An Examination of Harm Beliefs in Dog Fearful Children. Issue 2 (May 2016) - Byrne, Simon P.; Rapee, Ronald M.; Malhi, Gin S.; Sweller, Naomi; Hudson, Jennifer
This study examined the harm beliefs of dog fearful children and the effect of exposure therapy on harm beliefs. The harm beliefs of 27 dog fearful children were examined before and after exposure therapy to a dog. Children were shown a live dog and asked to rate the extent to which they believed the dog would harm them (for example, the dog would bite or attack). The children were asked to complete Behaviour Approach Tests (BATs) to the dog before and after the exposure therapy. The children partially endorsed all harm beliefs regarding the dog prior to exposure. Harm beliefs predicted distress during a BAT before exposure therapy and avoidance after exposure. There was a significant reduction in all harm beliefs after exposure therapy with large effect sizes. Results also indicate the effectiveness of a single session of exposure in reducing a child's harm beliefs.